Modal Analysis, Dynamic Properties and Horizontal Stabilisation of Timber Buildings - Edskär, Ida (Luleå tekniska universitet, Industriellt och hållbart byggande, 2019)
Engineers face new challenges as taller timber buildings are constructed. According to Eurocode 1-4, both horizontal deformations from static wind and acceleration levels shall be limited. Due to the low self-weight of wood, dynamic vibrations and acceleration levels cancause problems. The current knowledge in the field is limited and there is a need for increasing the understanding of dynamic properties in tall timber buildings. This research project has been a collaboration between Luleå Technical University and Sweco Structures AB, where the author has gained practical experience as a designer in parallel to the research studies. The purpose of this research is to understand and describe the dynamic behaviour of tall timber buildings using FE-simulations , studying their dynamic properties, and comparing acceleration levels to comfort criteria. By varying different parameters, dynamic properties have been studied and compared with assumptions and recommendations in Eurocode 1-4. In this study, buildings with cross-laminated timber panels (CLT) have been studied but also post-and-beam systems with trusses. Depending on the shape, layout and materials of the building, the dynamic properties of the building will vary: natural frequency, mode shape, modal mass, and modal stiffness. To assess the comfort of the building, the standard ISO 10137 has been used evaluating the natural frequency of the building and its peak acceleration. Simulations have been performed using finite element (FE) software where modal analyses have been performed. Over 250 simulations have been performed in this study. Adding mass reduces the natural frequency and the acceleration level of the building, which is an appropriate measure if the building has a frequency below 1 Hz. Increased stiffness increases the natural frequency and reduces the acceleration level, which is suitable for buildings with a natural frequency over 2 Hz. The empirical expression f = 46 / h should be used with caution as it is based onmeasurements of concrete and ...